The effects of cultivation patterns and nitrogen levels on fertility and bacterial community characteristics of surface and subsurface soil - Xu, Chengyu; Chen, Yuanjie; Zang, Qian; Li, Yulin; Zhao, Jinbiao; Lu, Xuanrui; Jiang, Min; Zhuang, Hengyang; Huang, Lifen (Frontiers in Microbiology, 2023)
The cropping system affects the physicochemical property and microbial community of paddy soil. Previous research mostly focused on the study of soil 0-20 cm underground. However, there may be difference in the laws of nutrient and microorganism distribution at different depths of arable soil. In surface (0-10 cm) and subsurface (10-20 cm) soil, a comparative analysis including soil nutrients, enzymes and bacterial diversity was carried out between the organic and conventional cultivation patterns, low and high nitrogen levels. Analysis results suggested that under the organic farming pattern, the contents of total nitrogen (TN), alkali-hydrolyzable nitrogen (AN), available phosphorus (AP) and soil organic matter (SOM) as well as alkaline phosphatase and sucrose activity increased in surface soil, but the SOM concentration and urease activity decreased in subsurface soil. A moderate reduction of nitrogen applied to soil could enhance soil enzyme activity. It was demonstrated by α diversity indices that high nitrogen levels remarkably undermined soil bacterial richness and diversity. Venn diagrams and NMDS analysis manifested great difference in bacterial communities and an apparent clustering tendency under different treatment conditions. Species composition analysis indicated that the total relative abundance of Proteobacteria, Acidobacteria and Chloroflexi retained stable in paddy soil. LEfSe results revealed that a low nitrogen organic treatment could elevate the relative abundance of Acidobacteria in surface soil and Nitrosomonadaceae in subsurface soil, thereby tremendously optimizing the community structure. Moreover, Spearman correlation analysis was also performed, which proved the significant correlation of diversity with enzyme activity and AN concentration. Additionally, redundancy analysis disclosed that the Acidobacteria abundance in surface soil and Proteobacteria abundance in subsurface soil exerted conspicuous influence on environmental factors and the microbial community structure. According to the findings of this study, it was believed that reasonable nitrogen application together with an organic agriculture cultivation system could effectively improve soil fertility in Gaoyou City, Jiangsu Province, China.